Anti-PD1/PD-L1 monotherapy vs standard of care in patients with recurrent or metastatic head and neck squamous cell carcinoma: A meta-analysis of randomized controlled trials. Issue 4 (29th January 2021) - Zhu, Peng; Wang, Yanwei; Zhang, Wendi; Liu, Xin
Abstract: Background: In recent years, a number of clinical trials for antibody drugs targeting programmed cell death protein 1 (PD1)/programmed cell death 1 ligand 1 (PD-L1) have been carried out on recurrent or metastatic head and neck squamous cell carcinoma (R/M SCCHN) and reported promising prospects. To further evaluate and understand the effects and risk of anti-PD1/PD-L1 monotherapy vs standard of care (SoC) in R/M SCCHN, we conducted this meta-analysis of published randomized controlled trials. Method: The potential eligible trials were searched from Cochrane library and Pubmed and Embase databases. Randomized controlled trials evaluating the effects and risk of anti-PD1/PD-L1 monotherapy vs SoC in platinum refractory R/M SCCHN were selected. The outcomes, including objective response rate, disease control rate, progression-free survival, overall survival, and treatment-related adverse events, were extracted and pooled. Results: 1345 patients with R/M SCCHN from three randomized controlled trials were enrolled in this analysis. Compared with SoC, anti-PD1/PD-L1 monotherapy could provide statistically significant overall survival benefit, hazard ratio (95% confidence interval ) = 0.79 [0.70–0.90]. However, we observed no significant difference between 2 treatments in progression-free survival (hazard ratio [95% confidence interval] = 0.96 [0.85–1.09]). Furthermore, anti-PD1/PD-L1 monotherapy caused less treatment-related adverse events than standard of care. Conclusion: Anti-PD1/PD-L1 monotherapy could indeed reduce the risk of death in R/M SCCHN patients, and provide higher safety vs SoC. Expression level of PD-L1 may be a useful biomarker for selecting patients with better response to anti-PD1/PD-L1 monotherapy.